Blade (2006), volume 1 ebook - Guggenheim, Marc (Blade (2006), 2014)
Collects Blade (2006) #1-6. A never before seen loom into Blade's mysterios past! Featuring Spider-Man, Dracula, Dr. Doom, Wolverine... and Santa Claus?